Desertifikation und mobile Tierhaltung in der Cholistan-Wüste (Süd-Punjab/Pakistan) - Scholz, Fred (ERDKUNDE, 1997)
In 1959 already, Carl Rathjens drew attention to the destruction of the natural basis for the existence of nomadic pastoralists in the Thar Desert of northwest India, yet this region has attracted little interest in the meantime. This is especially true for that part of the sand desert belonging to Pakistan and known as Cholistan. At the present time, the extent of desertification in the region can almost be called extreme. This is due, on the one hand, to the expansion of irrigated areas, thus reducing the land available to mobile livestock-keepers, and, on the other, to the shift towards cattle and small stock keeping and its rapid increase. This contribution takes the form of a report. Since 1967, the author has observed the processes of resource destruction, which he describes against the background of increased irrigation and the development of nomadic pastoralism. Special attention is paid to mobile nomadic cattle-keeping, which started to develop along with the increase in irrigated land. In the form observed here, it is definitely a particularity within Asia.